Controversy Between Anesthesiologists and Obstetricians on the Labor Ward: The Delphi Method is Used as a Consensus-building Technique. Issue 1 (March 2016) - Nguyen-Lu, N.; Downey, K.; Carvalho, J.C.A.
Abstract : ( Can J Anesth. 2015;62:271–277) Anesthesiologists and obstetricians try to ensure a safe and relatively painless experience for their delivering patients. However, practitioners of these 2 specialties vary in the ways they interpret the medical literature.